1) 2Na(+) + 2OH(-) + Mg(+2) + 2Cl(-) = Mg(OH)2 + 2Na(+) + 2Cl(-)
Mg(+2) + 2OH(-) = Mg(OH)2
2) 3Na(+) + 3OH(-) + Al(+3) + 3Cl(-) = Al(OH)3 + 3Na(+) + 3Cl(-)
Al(+3) + 3OH(-) = Al(OH)3
3) FeCl2 +2 NaOH = Fe(OH)2 + 2NaCl
Fe(+2) + 2Cl(-) + 2Na(+) + 2OH(-) = 2Na(+) + 2Cl(-) + Fe(OH)2
Fe(+2) + 2OH(-) = Fe(OH)2
4) Fe(+3) + 3Cl(-) + 3Ag(+) + 3NO3(-) = Fe(+3) + 3NO3(-) + 3AgCl
3Cl(-) + 3Ag(+) = 3AgCl
5) FeSO4 + 2NaOH = Fe(OH)2 + Na2SO4
Fe(+2) + SO4(-2) + 2Na(+) + 2OH(-) = Fe(OH)2 + 2Na(+) + SO4(-2)
Fe(+2) + 2OH(-) = Fe(OH)2
6) Fe(+2) + SO4(-2) +Ba(+2) + 2Cl(-) = Fe(+2) + 2Cl(-) + BaSO4
Ba(+2) + SO4(-2) = BaSO4
Объяснение:
1) 3HCl + Al(OH)3 = AlCl3 + 3H2O
3H(+) + 3Cl(-) + Al(OH)3 = Al(3+) + 3Cl(-) + 3H2O
3H(+) + Al(OH)3 = Al(3+) + 3H2O
2) 2HBr + H2SO4 = SO2 + 2H2O + Br2
2Br(-) -2e = Br2(0) 1 ок-ие
в-ль
S(+6) +2e = S(+4) 1 в-ие
ок-ль
S + 2HNO3 = H2SO4 + 2NO
S(0) -6e = S(+6) 1 ок-ие
в-ль
N(+5) +3e = N(+2) 2 в-ие
ок-ль
2NH3 + 2CrO3 = N2 + 3H2O + Cr2O3
2N(-3) -6e = N2(0) 1 ок-ие
в-ль
2Cr(+6) +6e = 2Cr(+3) 1 в-ие
ок-ль
3) CuCl2 + 2NaOH = Cu(OH)2↓ + 2NaCl
Cu(2+) + 2Cl(-) + 2Na(+) + 2OH(-) = Cu(OH)2↓ + 2Na(+) + 2Cl(-)
Cu(2+) + 2OH(-) = Cu(OH)2↓
BaCl2 + H2SO4 = BaSO4↓ + 2HCl
Ba(2+) + 2Cl(-) + 2H(+) + SO4(2-) = BaSO4↓ + 2H(+) + 2Cl(-)
Ba(2+) + SO4(2-) = BaSO4↓
Na2CO3 + 2HCl = 2NaCl + CO2↑ + H2O
2Na(+) + CO3(2-) + 2H(+) + 2Cl(-) = 2Na(+) + 2Cl(-) + CO2↑ + H2O
CO3(2-) + 2H(+) = CO2↑ + H2O